Tissue Culture-Induced Heritable Genomic Variation in Rice, and Their Phenotypic Implications - Zhang, Di (Public Library of Science, 2014)
BACKGROUND: Somaclonal variation generally occurs in plants regenerated from tissue culture. However, fundamental issues regarding molecular characteristics, mutation rates and mutation spectra of plant somatic variation as well as their phenotypic relevance have been addressed only recently. Moreover, these studies have reported highly discrepant results in different plant species and even in the same plant genotype. METHODOLOGY/PRINCIPAL FINDINGS: We investigated heritable genomic variation induced by tissue culture in rice by whole genome re-sequencing of an extensively selfed somaclonal line (TC-reg-2008) and its wild type (WT) donor (cv. Hitomebore). We computed the overall mutation rate, single nucleotide polymorphisms (SNPs), small scale insertions/deletions (Indels) and mobilization of transposable elements (TEs). We assessed chromosomal distribution of the various types of genomic variations, tested correlations between SNPs and Indels, and examined concomitancy between TE activity and its cytosine methylation states. We also performed gene ontology (GO) analysis of genes containing nonsynonymous mutations and large-effect mutations, and assayed effects of the genomic variations on phenotypes under both normal growing condition and several abiotic stresses. We found that heritable somaclonal genomic variation occurred extensively in rice. The genomic variations distributed non-randomly across each of the 12 rice chromosomes, and affected a large number of functional genes. The phenotypic penetrance of the genomic variations was condition-dependent. CONCLUSIONS/SIGNIFICANCE: Tissue culture is a potent means to generate heritable genetic variations in rice, which bear distinct difference at least in space (chromosomal distribution) from those occurred under natural settings. Our findings have provided new information regarding the mutation rate and spectrum as well as chromosomal distribution pattern of somaclonal variation in rice. Our data also suggest that rice possesses a strong capacity to canalize genetic variations under normal growing conditions to maintain phenotypic robustness, which however can be released by certain abiotic stresses to generate variable phenotypes.